PSYCHOTECHNICS IN ACTING SKILLS. - Urazimbetova Shakhsanem (TADQIQOTLAR.UZ, 2024)
Abstract: Psychotechnics in acting skills refer to the various techniques and approaches employed by actors to access and convey emotions effectively in their performances. This article explores the concept of psychotechnics in acting, highlighting key aspects such as emotional recall, subtext, triggers, listening, improvisation, vulnerability, release techniques, and more. These psychotechnics allow actors to tap into their emotional depth, create authentic portrayals, and connect with audiences on a profound level. The article emphasizes the importance of emotional context, stamina, anchoring, adaptability, and resilience in the actor's craft. By mastering psychotechnics, actors can enhance their range, authenticity, and impact as performers.